Cucurbiturils : chemistry, supramolecular chemistry, and applications - Kim, Kimoon (World Scientific, 2018)
This book chronicles the history and development of cucurbiturils. It provides a general introduction and a field-wide overview of the synthesis, properties and applications of cucurbiturils.Beginning with a chronicled history in the development of the once little-known peculiarity to the forefront of supramolecular chemistry, followed by an in depth look at the preparation, properties and host-guest chemistry, the title showcases the uses of cucurbiturils in chemistry, materials science and biology.An essential resource for both new and experienced researchers, as it provides an overview of the diverse applications, new methodologies and research, as well as challenges in the field.- Resumé vydavatel